The Politics of the Sacred in America The Role of Civil Religion in Political Practice - Squiers, Anthony (Springer International Publishing, 2018)
This book provides a comprehensive investigation of the political dimensions of civil religion in the United States. By employing an original social-psychological theory rooted in semiotics, it offers a qualitative and quantitative empirical examination of more than fifty years of political rhetoric. Further, it presents two in-depth case studies that examine how the cultural, totemic sign of 'the Founding Fathers' and the signs of America's sacred texts (the Constitution and the Declaration of Independence) are used in attempts to link partisan policy positions with notions that the country collectively holds sacred. The book's overarching thesis is that America's civil religion serves as a discursive framework for the country's politics of the sacred, mediating the demands of particularistic interests and social solidarity through the interaction of social belief and institutional politics like elections and the Supreme Court. The book penetrates America's unique political religiosity to reveal and unravel the intricate ways in which politics, political institutions, religion and culture intertwine in the United States. .